2023
DOI: 10.3390/antibiotics12060963
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and Semisynthetic Compounds as Antibacterials Targeting Virulence Traits in Resistant Strains: A Narrative Updated Review

Abstract: This narrative review paper provides an up-to-date overview of the potential of novel synthetic and semisynthetic compounds as antibacterials that target virulence traits in resistant strains. The review focused on research conducted in the last five years and investigated a range of compounds including azoles, indoles, thiophenes, glycopeptides, pleuromutilin derivatives, lactone derivatives, and chalcones. The emergence and spread of antibiotic-resistant bacterial strains is a growing public health concern, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 118 publications
0
8
0
Order By: Relevance
“…This circumstance, among others, determines the need to create synthetic compounds having similar antibacterial properties, but devoid of AMP’s shortcomings. Detailed analyses of various classes of synthetic compounds that can be used to solve this problem are given in [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This circumstance, among others, determines the need to create synthetic compounds having similar antibacterial properties, but devoid of AMP’s shortcomings. Detailed analyses of various classes of synthetic compounds that can be used to solve this problem are given in [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we synthesized a compound "DL 4 12" (Figure 1), in which quaternary residues of 1,4-diazabicyclo[2.2.2]octane (DABCO) were connected by tetramethylene linker with a dodecane substituent, and showed its high antibacterial activity [6]. This class of compounds was not mentioned in the detailed review by Stojkovic et al [39], published in May 2023. In this work, for the first time, we showed that the polycationic amphiphile DL 4 12 directly interacts with the S. aureus cell wall, starting a pronounced disruption of its structure.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics 2024, 13, x FOR PEER REVIEW 8 of 25 1 Compound number used in text; numbers are registered based on retention times (Rt), i.e., order of elution of compounds on SB-Aq column. 2 Detected only in the fruits MFDE.…”
Section: Fatty Acid Phytosterol and Triterpene Composition Of Ch 2 Cl...mentioning
confidence: 99%
“…In an era of growing antimicrobial resistance, it is crucial to discover new antibacterial and antifungal agents [1,2]. Plants are well-known to be rich sources of compounds, which have a wide range of biological activities, including effects on broad spectrum of microorganisms [3], the most researched plant preparations are essential oils and extracts [4].…”
Section: Introductionmentioning
confidence: 99%
“…These families have been assigned to three priority groups, comprising critical pathogens ( Acinetobacter , Pseudomonas , and Enterobacteriaceae ), high priority pathogens ( Enterococcus faecium , Staphylococcus aureus , Helicobacter pylori , Campylobacter , Salmonella spp., and Neisseria gonorrhoeae ), and medium priority pathogens ( Streptococcus pneumoniae , and Shigella spp.) [ 3 , 4 ]. Resistance in bacteria can be acquired or natural, but several mechanisms exist by which pathogens can become resistant to antibiotics ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%